Temperature, size and developmental plasticity in birds. (7th December 2022) - Weeks, Brian C.; Klemz, Madeleine; Wada, Haruka; Darling, Rachel; Dias, Tiffany; O'Brien, Bruce K.; Probst, Charlotte M.; Zhang, Mingyu; Zimova, Marketa
Abstract : As temperatures increase, there is growing evidence that species across much of the tree of life are getting smaller. These climate change-driven size reductions are often interpreted as a temporal analogue of the observation that individuals within a species tend to be smaller in the warmer parts of the species' range. For ectotherms, there has been a broad effort to understand the role of developmental plasticity in temperature–size relationships, but in endotherms, this mechanism has received relatively little attention in favour of selection-based explanations. We review the evidence for a role of developmental plasticity in warming-driven size reductions in birds and highlight insulin-like growth factors as a potential mechanism underlying plastic responses to temperature in endotherms. We find that, as with ectotherms, changes in temperature during development can result in shifts in body size in birds, with size reductions associated with warmer temperatures being the most frequent association. This suggests developmental plasticity may be an important, but largely overlooked, mechanism underlying warming-driven size reductions in endotherms. Plasticity and natural selection have very different constraining forces, thus understanding the mechanism linking temperature and body size in endotherms has broad implications for predicting future impacts of climate change on biodiversity.